The Legal Protection in Crime of E-Commerce Transactions - Muhammad Citra Ramadhan; Dahlia Kusuma Dewi; Yasmirah Mandasari Saragih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
The E-commerce can usually be carried out between business actors, marketplace owners and also with consumers, including the use of the internet and the World Wide Web which is used to sell products and services for consumers. The provisions of Article 1 point 2 of Act No. 11 of 2008 in conjunction with Act No. 19 of 2016 Concerning Electronic Information and Transactions, state that electronic transactions are legal acts carried out using computers, computer networks or electronic media. Electronic buying and selling transactions (E-Commerce) is one of the embodiments of the provisions above. The type of research used in this study is the normative juridical type. The normative juridical research method is a research method that refers to the legal norms contained in laws and regulations. The research used in this research is descriptive analytical research. The classification of prohibited acts in the ITE Law is regulated in nine articles, from Article 27 to Article 37. The construction of these articles regulates in more detail the development of traditional crime modes as stated in the Criminal Code (KUHP). Buying and selling transactions, even though they are carried out online, based on the ITE Law and PP PSTE are still recognized as electronic transactions that can be accounted for. The Electronic Contract itself according to Article 48 paragraph (3) PP PSTE must at least contain the following matters; party identity data; object and specification; Electronic Transaction requirements; prices and fees; procedures in the event of cancellation by the parties; provisions that give the right to the aggrieved party to be able to return the goods and/or request a product replacement if there are hidden defects; and the choice of law for settlement of Electronic Transactions.